Eyelid edema in relapsing polychondritis - Anshul Goel; Arun Gogna (Indian Journal of Rheumatology)
Relapsing polychondritis (RP) is a multisystem inflammatory disease affecting all types of cartilage and proteoglycan-rich tissues with recurrent bouts of inflammation resulting in tissue damage. The pleomorphic nature, the wide spectrum of clinical features and insidious onset of the disease makes the diagnosis of RP a challenge for clinicians. Eyelid edema is a recognized manifestation of this disease frequently in association with inflammation in other parts of eyes. This case highlights eyelid edema in a patient who presented primarily with chondritis of the pinna, which subsided with steroids.